The Coordinated Action of MYB Activators and Repressors Controls Proanthocyanidin and Anthocyanin Biosynthesis in Vaccinium - Lafferty, Declan J.; Espley, Richard V.; Deng, Cecilia H.; Dare, Andrew P.; Günther, Catrin S.; Jaakola, Laura; Karppinen, Katja; Boase, Murray R.; Wang, Lei; Luo, Henry; Allan, Andrew C.; Albert, Nick W. (Frontiers in Plant Science, 2022)
Vaccinium berries are regarded as ‘superfoods’ owing to their high concentrations of anthocyanins, flavonoid metabolites that provide pigmentation and positively affect human health. Anthocyanin localization differs between the fruit of cultivated highbush blueberry (V. corymbosum) and wild bilberry (V. myrtillus), with the latter having deep red flesh coloration. Analysis of comparative transcriptomics across a developmental series of blueberry and bilberry fruit skin and flesh identified candidate anthocyanin regulators responsible for this distinction. This included multiple activator and repressor transcription factors (TFs) that correlated strongly with anthocyanin production and had minimal expression in blueberry (non-pigmented) flesh. R2R3 MYB TFs appeared key to the presence and absence of anthocyanin-based pigmentation; MYBA1 and MYBPA1.1 co-activated the pathway while MYBC2.1 repressed it. Transient overexpression of MYBA1 in Nicotiana benthamiana strongly induced anthocyanins, but this was substantially reduced when co-infiltrated with MYBC2.1. Co-infiltration of MYBC2.1 with MYBA1 also reduced activation of DFR and UFGT, key anthocyanin biosynthesis genes, in promoter activation studies. We demonstrated that these TFs operate within a regulatory hierarchy where MYBA1 activated the promoters of MYBC2.1 and bHLH2. Stable overexpression of VcMYBA1 in blueberry elevated anthocyanin content in transgenic plants, indicating that MYBA1 is sufficient to upregulate the TF module and activate the pathway. Our findings identify TF activators and repressors that are hierarchically regulated by SG6 MYBA1, and fine-tune anthocyanin production in Vaccinium. The lack of this TF module in blueberry flesh results in an absence of anthocyanins.